2005
DOI: 10.1056/nejmoa044238
|View full text |Cite
|
Sign up to set email alerts
|

EGFRMutation and Resistance of Non–Small-Cell Lung Cancer to Gefitinib

Abstract: Mutations of the epidermal growth factor receptor (EGFR) gene have been identified in specimens from patients with non-small-cell lung cancer who have a response to anilinoquinazoline EGFR inhibitors. Despite the dramatic responses to such inhibitors, most patients ultimately have a relapse. The mechanism of the drug resistance is unknown. Here we report the case of a patient with EGFR-mutant, gefitinib-responsive, advanced non-small-cell lung cancer who had a relapse after two years of complete remission duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

39
2,831
9
30

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 3,664 publications
(2,940 citation statements)
references
References 23 publications
39
2,831
9
30
Order By: Relevance
“…Structural modeling and biochemical studies showed that this second mutation led to gefitinib resistance. 182 The same mutation was confirmed by Pao et al 208 through molecular analysis of EGFR in patients with acquired resistance to gefitinib or erlotinib. These gefitinib-resistant cases contain the same secondary mutation (T790M) in the kinase domain as those reported by Kobayashi et al 182 Codon 790 of EGFR is considered to be the 'gatekeeper' residue, which is an important determinant of inhibitor affinity in the ATP-binding pocket of EGFR.…”
Section: Acquired Resistance To Egfr Tkimentioning
confidence: 77%
See 3 more Smart Citations
“…Structural modeling and biochemical studies showed that this second mutation led to gefitinib resistance. 182 The same mutation was confirmed by Pao et al 208 through molecular analysis of EGFR in patients with acquired resistance to gefitinib or erlotinib. These gefitinib-resistant cases contain the same secondary mutation (T790M) in the kinase domain as those reported by Kobayashi et al 182 Codon 790 of EGFR is considered to be the 'gatekeeper' residue, which is an important determinant of inhibitor affinity in the ATP-binding pocket of EGFR.…”
Section: Acquired Resistance To Egfr Tkimentioning
confidence: 77%
“…182 The same mutation was confirmed by Pao et al 208 through molecular analysis of EGFR in patients with acquired resistance to gefitinib or erlotinib. These gefitinib-resistant cases contain the same secondary mutation (T790M) in the kinase domain as those reported by Kobayashi et al 182 Codon 790 of EGFR is considered to be the 'gatekeeper' residue, which is an important determinant of inhibitor affinity in the ATP-binding pocket of EGFR. 110 Substitution of this residue in EGFR with a bulky methionine may cause resistance by steric interference with binding of TKIs, including gefitinib and erlotinib.…”
Section: Acquired Resistance To Egfr Tkimentioning
confidence: 77%
See 2 more Smart Citations
“…It would be a primary reason of failure to some extent 63. Besides, the EGFR T790M mutation could be another important mechanism for resistance to EGFR TKIs 64. Repeated biopsy showed that it may be responsible for half of acquired resistance cases 65.…”
Section: The Mechanism Of Brain Metastasismentioning
confidence: 99%